The use of fitness centre apps and its relation to customer satisfaction: A UTAUT2 perspective - Barbosa, Helena Ferreira (2022)
Purpose The purpose of this paper is to analyse the intention of using fitness app made available by the fitness centre to its members and their relationship with overall customer satisfaction. Design/methodology/approach The present study uses the extended unified theory of acceptance and use of technology (UTAUT2) as the base model. All the hypothesised relationships were tested through partial least square structural equation modelling (PLS-SEM), in a quantitative study with data from 1,676 fitness consumers from Portugal. Findings The results support the ability of UTAUT2 in predicting the customer´s intention to use the fitness app. Performance expectancy, effort expectancy, social influence, facilitating conditions, hedonic motivation and habit have a positive impact on behavioural intentions to use the fitness app. Performance expectancy and habit have the strongest relationships. Behavioural intentions are positively related both to the usage behaviour of the fitness app and to overall customer satisfaction. Practical implications The results of this study present a strong contribution for fitness centre managers, since it highlights the importance of using these apps as a way to increase customer satisfaction, increasing retention levels. Originality/value This study is paramount as regards to examine the behavioural intention to use the fitness apps that the fitness centres make available to their members using UTAUT2 model.